2006
DOI: 10.1103/physrevlett.97.137001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Field Enhancement of Superconductivity in Ultranarrow Wires

Abstract: We study the effect of an applied magnetic field on sub-10nm wide MoGe and Nb superconducting wires. We find that magnetic fields can enhance the critical supercurrent at low temperatures, and does so more strongly for narrower wires. We conjecture that magnetic moments are present, but their pair-breaking effect, active at lower magnetic fields, is suppressed by higher fields. The corresponding microscopic theory, which we have developed, quantitatively explains all experimental observations, and suggests tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
90
5

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(109 citation statements)
references
References 23 publications
14
90
5
Order By: Relevance
“…These results are in agreement with Monte Carlo simulations (67) which found z = 1.97(3), z + η = 1.985 (20) and ν = 0.689 (6).…”
Section: Scaling Analysissupporting
confidence: 82%
“…These results are in agreement with Monte Carlo simulations (67) which found z = 1.97(3), z + η = 1.985 (20) and ν = 0.689 (6).…”
Section: Scaling Analysissupporting
confidence: 82%
“…It has since been shown that such a theory applies in a large variety of situations with 'pair-breaking' perturbations: anisotropic superconductors with non-magnetic impurities [15], lower-dimensional superconductors with magnetic fields oriented in a direction parallel to the Cooper pair motion [16], and s-wave superconductors with inhomogeneity in the strength of the attractive BCS interaction [17]. Indeed, it is expected that pair-breaking is present in any experimentally realizable SMT at T = 0: in the nanowire experiments, explicit evidence for pairbreaking magnetic moments on the wire surface was presented recently by Rogachev et al [13].Fluctuations about the AG theory have been considered [16,18,19] in the metallic state, and lead to the well-known Aslamazov-Larkin (AL), Maki-Thomson (MT) and Density of States (DoS) corrections to the conductivity. At the SMT, field-theoretic analyses [20,21] show that the AG theory, along with the AL, MT and DoS corrections, is inadequate in spatial dimension d ≤ 2, and additional self-interactions among Cooper pairs have to be included.…”
mentioning
confidence: 99%
“…It has since been shown that such a theory applies in a large variety of situations with 'pair-breaking' perturbations: anisotropic superconductors with non-magnetic impurities [15], lower-dimensional superconductors with magnetic fields oriented in a direction parallel to the Cooper pair motion [16], and s-wave superconductors with inhomogeneity in the strength of the attractive BCS interaction [17]. Indeed, it is expected that pair-breaking is present in any experimentally realizable SMT at T = 0: in the nanowire experiments, explicit evidence for pairbreaking magnetic moments on the wire surface was presented recently by Rogachev et al [13].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of localized magnetic moments in semiconductor heterostructures and devices are known to be carried by structural defects with unpaired electrons [1]. Localized magnetic moments were recently detected on the surface of a normal metal [2]; in superconducting systems, they are believed to be responsible for several unusual effects such as 1/f noise in SQUIDs and qubits [3] and an anomalous magnetic field enhancement of a critical current in nanowires [4]. The origin of spontaneously formed magnetic moments often remains unknown; on the other hand, their effects can be probed by magnetic moments that are introduced intentionally.…”
Section: Introductionmentioning
confidence: 99%